Container terminal berth planning - Theofanis, S.; Boile, M.; Golias, Mihalis (My University, 2009)
A comparative, up-to-date, critical review of existing research efforts relating to berth planning is presented. Existing models are critically reviewed on the basis of their efficiency in addressing key operational and tactical questions relating to vessel service and their relevance and applicability to different marine terminal operator berth-planning strategies and contractual service arrangements between terminal operators and ocean carriers. The strengths and deficiencies of the existing models in addressing real-world problems in a systemic and coherent manner are discussed. The paper concludes with some insights for future research issues.